Multivariate Analysis of Nepalese Non-life Insurers’ Performance: Evidence from the CARAMEL Framework - Karki, Dipendra; Dutta, Bibek; Dahal, Rewan Kumar; Ghimire, Binod; Joshi , Surendra Prasad (Nepalese Journal of Insurance and Social Security, 2025)
Purpose: This study conducts a comprehensive multivariate evaluation of financial performance among selected Nepalese non-life insurers using the CARAMEL framework over the 2013/14–2021/22 period. It examines the influence of key financial dimensions on ROA and ROE, identifies patterns of strength and vulnerability, assesses the temporal stability of performance indicators, and develops a benchmarking tool tailored to Nepal’s evolving insurance landscape. Design/methodology/approach: A causal-comparative research design is employed, utilizing panel data from 19 pre-merger non-life insurance companies over nine fiscal years (2013/14–2021/22). in Nepal from 2014 to 2022. Secondary data were analyzed using multivariate panel regression models. Findings: Results show that capital adequacy, asset quality, management efficiency, and liquidity significantly influence financial performance, while the effects of reinsurance and earnings remain inconclusive. Conclusion: The study advances the understanding of financial performance evaluation in Nepal’s non-life insurance sector by leveraging the CARAMEL framework and multivariate panel data analysis. The findings highlight the critical roles of capital adequacy, asset quality, and management efficiency in driving insurer performance, while the roles of reinsurance and earnings remain ambiguous, reflecting deeper institutional and operational constraints. Implications: The study aspires to contribute meaningfully to the academic discourse and practical decision-making in the field of insurance management, empirically validate a multivariate framework that equips regulators, insurers, and policymakers in Nepal with actionable insights to enhance financial resilience, strategic decision-making, and sectoral governance. Originality/value: The study advances insurance performance analysis by linking multidimensional financial indicators within the CARAMEL framework to profitability outcomes, offering a holistic understanding of the drivers behind insurer resilience and growth. JEL Classification: G22, G32, C33, L25